DESKRIPSI SMA DAN SMK DI KABUPATEN MINAHASA TENGGARA BERDASARKAN INDIKATOR STANDAR NASIONAL PENDIDIKAN BERBASIS EVALUASI DIRI SEKOLAH (Standar Kompetensi Lulusan, Standar Isi, Standar Proses, Standar Pendidik dan Tenaga Kependidikan) - Stefano Kasal Taarega; Djoni Hatidja; Marline S Paendong (JURNAL ILMIAH SAINS, 2016)
DESKRIPSI SMA DAN SMK DI KABUPATEN MINAHASA TENGGARA BERDASARKAN INDIKATOR STANDAR NASIONAL PENDIDIKAN BERBASIS EVALUASI DIRI SEKOLAH (Standar Kompetensi Lulusan, Standar Isi, Standar Proses, Standar Pendidik dan Tenaga Kependidikan) ABSTRAK Tujuan penelitian ini adalah: Mendeskripsikan Sekolah Menengah Atas/Sekolah Menengah Kejuruan (SMA/SMK) di Kabupaten Minahasa Tenggara berdasarkan 4 Standar Nasional Pendidikan (Standar Kompetensi Lulusan, Standar Isi, Standar Proses, Standar Pendidik dan Tenaga Kependidikan) yang berbasis Evaluasi Diri Sekolah (EDS). Gambaran umum SMA dan SMK berdasrkan peubah-peubah standar pendidikan diharapkan dapat memberikan informasi tentang mutu masing-masing SMA dan SMK dikabupaten Minahasa Tenggara. Penelitian ini akan dilaksanakan dengan mengambil data primer di 11 SMA/SMK yang berada di Kabupaten MITRA.  Masing-masing sekolah dilakukan wawancara terhadap 5 guru dan Kepala Sekolah dengan kuisioner berbasis Evaluasi Diri Sekolah. Peubah-peubah yang diamati adalah Standar Kompetensi Lulusan, Standar Isi, Standar Proses, Standar Pendidikan dan Tenaga Kependidikan. Data akan dianlisis dengan menggunakan perangkat lunak Komputer. Hasilnya, menunjukan bahwa SMA Negeri 1 Ratahan (S2), SMA Negeri 2 Ratahan (S3), SMK Negeri 1 Ratahan (S4), SMA Negeri 1 Touluaan (S5), SMK Negeri 1 Touluaan (S6), SMA Negeri 1 Belang (S9), SMA Negeri 1 Posumaen (S10), SMK Nasional Malompar (S12) memiliki karateristik penilaian yang hampir sama pada Standar Pendidik dan Tenaga Kependidikan. Kata kunci:      SMA, SMK, Evaluasi Diri Sekolah, Kepala Sekolah, Guru, Kabupaten Minahasa Tenggara   DESCRIPTION OF SENIOR HIGH SCHOOL (SHS) AND VOCATIONAL SCHOOL (VS) IN SOUTHEAST MINAHASA REGENCY BASED ON INDICATOR OF NATIONAL STANDARDS OF EDUCATION BASED SCHOOL’S SELF-EVALUATION (Standards of Graduates Competency, Content Standards, Process Standards,  Standards of Administrative and Education Personnel)   ABSTRACT The purpose of this study is to describe the Senior High School/Vocational High School (SMA/SMK) in Southeast Minahasa Regency by 4 National Education Standards (Standards of Graduates Competency, Content Standards, Process Standards, standards of Administrative and Education Personnel) based school’s Self-Evaluation. General overview of SHS and VS based on those variables educational standards was expected to provide the information about the quality of each senior high school and vocational high school in Southeast Minahasa Regency. This study would be conducted by taking the primary data in 11 senior high school/vocational school located in the district of Southeast Minahasa.  Each school conducted interviews with five teachers and headmasters with the School Self-Evaluation-based questionnaire. Variables measured were standards of Graduates Competency, Content Standards, Process Standards, and Standards of administrative  and Education Personnel. Data analysis will using the computer software. As a result, show that Public Senior High School 1 of Ratahan (S2), Public Senior High School 2 of Ratahan (S3), Public Vocational School 1 of Ratahan (S4), Public Senior High School 1 of Touluaan (S5), Public Vocational School 1 of Touluaan (S6), Public Senior High School 1 of Belang (S9 ), Public Senior High School 1 of Posumaen (S10), the National Vocational School of Malompar (S12) has characteristics similar ratings on Standards of administative and Education Personnel. Retrieved also that Variables Graduates Competency Standards, Content Standards, Process Standard, Standards of administrative and Education Personnel, which does not significantly influence the Dependent Variabel  that is School Accreditation. Keywords: Senior High School, Vocational High School, School’s self-evaluation, Headmaster, Teacher, Southeast Minahasa Region